Pengaruh Lama Fermentasi Kepala Ikan Tongkol Abu dan Sawi Putih sebagai Pakan Larva Black Soldier Fly dalam Mereduksi Sampah Organik - Syani, Mutiara; Rizkawati, Vina; Suhatma, Reny; Supriyatin, Supriyatin (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Black Soldier Fly (BSF) larvae are larvae that are able to decompose and convert various types of organic waste including kitchen waste, vegetables, fruits, bread, and fermented foods. The purpose of this study was to determine the effect of fermentation time, optimum time, and environmental factors in the form of pH to reduce ash mackerel head waste and white mustard greens by black soldier fly larvae. The study was conducted from July 1 to September 30, 2024, located at the BSF Maggot House. Based on the research that has been done, it is known that F3 is the treatment that has the largest WRI value of 5.33% and has a superior length and weight compared to other treatments. Fermented feed can affect the reduction value of organic waste compared to non-fermented feed, and the optimum fermentation time to be given to BSF larvae is three days. Furthermore, the study found that highly acidic conditions, specifically a pH of 4, adversely affected the larvae's survival rate, resulting in a higher mortality rate.